Table of Content - - (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content:1. The field of intelligence study in academic institutions: A comparative analytical study of American and British intelligence studiesDr. Mohamed Elzin Mohamed Ahmed Ibrahim2. The effectiveness of the Madrasati platform according to the Needham constructivist model  in increasing achievement of second-year intermediate female students in the TIMSS tests (algebra field) and the teacher’s point of viewMariam Farhan Alfifi, Ghada Owaid Awad Al-Sahli3. Social support programs: its effects on girls schooling and reducing dropping out of school in the northeast middle Atlas – MoroccoMr. Abdelilah El-Alami, Prof. Dr. Jaouad El-Bazoui, Prof. Dr. Abdelouahed Bouberria4. The growing influence of China in the Middle East and its implications for US relationsDr. Khaldoun Abdul Samad5. Balfour's Legacy: Britain, Zionism, and the Controversial Path to Israel's EstablishmentAli Mohammed Qader6. The Impact of Organizational Citizenship on Job Performance of Employees in the Private Automotive Sector in Saudi Arabia in light of 2030’s visionMr. Ahmed Farouk Ali, Dr. Elsayed Eid, Dr. Heba Alhadad
Keywords: Arab Journal of Sciences & Research Publishing